Why So Few Women and Minorities in Local Politics?: Incumbency and Affinity Voting in Low Information Elections. Issue 2 (3rd April 2017) - McGregor, R. Michael; Moore, Aaron; Jackson, Samantha; Bird, Karen; Stephenson, Laura B.
Abstract : Previous research has examined the effects of incumbency or affinity voting on the political representation of women and minorities. No study has considered the interaction of these two factors, even though there are good reasons to suspect that both may play a key role in voter choice. This study examines the joint effects of incumbency and gender and racial affinity voting in non-partisan and generally low information ward elections in the City of Toronto. Results reveal the absence of gender affinity effects, regardless of the presence of an incumbent, but that racial affinity is a factor in wards without incumbents.